Association of work productivity with clinical and patient‐reported factors in patients infected with hepatitis C virus. Issue 8 (14th March 2016) - Younossi, Z. M.; Stepanova, M.; Henry, L.; Younossi, I.; Weinstein, A.; Nader, F.; Hunt, S.
Summary: Patients with HCV infection have reduced work productivity (WP), in terms of both presenteeism (impairment in work productivity while working) and absenteeism (productivity loss due to absence from work). The aim of this study was to identify clinical and patient‐reported factors that are predictive of WP in HCV‐infected patients. HCV‐infected patients enrolled in clinical trials completed 3 PRO questionnaires (CLDQ‐HCV, SF‐36 and FACIT‐F) and one work productivity (WPAI:SHP) questionnaire. In employed subjects, work productivity and its absenteeism and presenteeism components were calculated using WPAI:SHP instrument. Of 4121 HCV‐infected patients with work productivity data, 2480 (60.2%) reported to be employed, and of those, 2190 had completed all PRO questionnaires before treatment initiation. Of the study cohort, 519/2190 (23.7%) had severe work impairment. In multiple linear regression analysis, work productivity was predicted by lower scores in activity/energy domain of CLDQ‐HCV, physical well‐being domain of FACIT‐F, worry domain of CLDQ‐HCV and role physical domain of SF‐36 (all P < 0.0005). Furthermore, presenteeism was independently predicted by the activity/energy of CLDQ‐HCV, physical well‐being of FACIT‐F, worry domain of CLDQ‐HCV, role physical scale of SF‐36 and fatigue scale of FACIT‐F ( P < 0.002). Finally, absenteeism was independently predicted by physical well‐being scale of FACIT‐F and role physical scale of SF‐36 (all P < 0.002). Clinically, work productivity impairment was predicted by the presence of cirrhosis, anxiety, depression and clinically overt fatigue ( P < 0.01). Thus, the most important drivers of WP in HCV are impairment of physical aspects of PROs and clinical history of depression, anxiety, fatigue and cirrhosis.